Wastewater monitoring of COVID-19: a perspective from Scotland. (14th December 2022) - Fang, Zhou; Roberts, Adrian M. I.; Mayer, Claus-Dieter; Frantsuzova, Anastasia; Potts, Jackie M.; Cameron, Graeme J.; Singleton, Peter T. R.; Currie, Iona
Abstract: Scotland introduced wastewater monitoring for COVID-19 early in the pandemic. From May 2020, samples have been taken and analysed using quantitative polymerase chain reaction (qPCR). The programme was expanded to over 100 sites accounting for around 80% of the population. Data are presented publicly via a dashboard and regular reports are produced for both the public and health professionals. Wastewater-based epidemiology (WBE) offers opportunities and challenges. It offers an objective means of measuring COVID-19 prevalence and can be more practical or timely than other methods of mass testing. However, it also has substantial variability impacted by multiple environmental factors. Methods for data collection and analysis have developed significantly through the pandemic, reflecting the evolving situation and policy direction. We discuss the Scottish experience of wastewater monitoring for COVID-19, with a focus on the analysis of data. This includes our approach to flow normalisation, our experience of variability in measurements and anomalous values, and the visualisation and presentation of data to stakeholders. Summarising the Scottish methodology as of March 2022, we also discuss how wastewater data were used for informing policy and public health actions. We draw lessons from our experience and consider future directions for WBE in Scotland. HIGHLIGHTS: The Scottish COVID-19 WBE programme covered around 80% of the population with regular COVID-19 wastewater testing for over a year. WBE reports complemented case data to assist policymakers and other stakeholders. Techniques and decisions (e.g. normalisation and visualisation) were driven by changing context and feedback. The practical pros and cons of WBE were made apparent, suggesting future directions. Graphical Abstract